2010
DOI: 10.1136/jamia.2009.000505
|View full text |Cite
|
Sign up to set email alerts
|

The design and evaluation of a graphical display for laboratory data

Abstract: Data presentation format can affect how physicians interpret laboratory data. Graphic displays have several advantages over numeric displays but are not always optimal. User, task and data characteristics should be considered when designing information displays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 33 publications
1
60
0
1
Order By: Relevance
“…One logical direction to pursue is the graphical representation of numerical data 45. One usability study found that graphical laboratory value displays led to reduced review times and that graphical and tabular representations were each more effective for answering different clinical questions 46. However, different clinical settings may benefit from differing data summary formats.…”
Section: Resultsmentioning
confidence: 99%
“…One logical direction to pursue is the graphical representation of numerical data 45. One usability study found that graphical laboratory value displays led to reduced review times and that graphical and tabular representations were each more effective for answering different clinical questions 46. However, different clinical settings may benefit from differing data summary formats.…”
Section: Resultsmentioning
confidence: 99%
“…There were efforts made by Bauer et al [3] to enhance a physician's throughput by the means of an alternative visualization of the laboratory reports. In a study done by Torsvik et al [4], it was observed that alternative visualizations of laboratory test reports helped clinicians in few special cases.…”
Section: Introductionmentioning
confidence: 99%
“…There is a need to present quality data in a more effective way as the risk of it being misunderstood or not used at all is well recognised 3. Graphic display may make interpretation easier as presenting data visually is known to amplify cognition by capitalising on human perceptual capabilities 4. Graphic display, with several quality domains to capture, is not easy to design.…”
Section: Introductionmentioning
confidence: 99%